The study of an acute toxicity of extracts from Veronica teucrium L. and from Veronica longifolia L. - А. Р. Osmachko; V. M. Ivanochko; A. M. Kovaleva; T. V. Ilyina; O. M. Koshovyi (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of our work were to study the acute toxicity of extracts obtained from herb, leaves, flowers of V. teucrium L. and from herb of V. longifolia L.